The Effects of Early Antibiotic Administration on Bacterial Culture Growth From Hand Abscesses. (June 2016) - Trionfo, Arianna; Thoder, Joseph J.; Tosti, Rick
Background: Traditional management of hand abscesses consists of withholding antibiotics prior to drainage to optimize bacterial culture growth and outcome. The purpose of this study was to determine the effect of preoperative empiric antibiotics on the rate of culture growth and rate of adverse events in patients with acute hand abscesses.Methods: We performed a retrospective review of prospectively collected data on 88 consecutive hand abscesses that received empiric antibiotics prior to incision and drainage from 2012 to 2013 at an urban academic institution. We analyzed patient demographics, bacteriology, culture growth results, time to surgery, and frequency of adverse events.Results: The overall rate of positive culture growth was 90% (n = 79) despite running the antibiotics for a mean of 31 hours prior to debridement. Furthermore, 96% of the isolates were given a susceptible antibiotic during that time. The mean number of debridements was 1.5 per patient, but 4 re-operations were necessary for wound complications. No patients required an amputation or were upgraded to intensive care.Conclusions: Preoperative empiric antibiotic administration does not appear to greatly reduce bacterial culture growth from hand abscesses. The adverse events are relatively few for simple abscesses treated with pre-surgical antibiotics and decompression within 24 hours.